Binary graphene-based cathode structure for high-performance lithium-sulfur batteries. (9th January 2020) - Fang, Ruopian; Zhao, Shiyong; Chen, Ke; Wang, Da-Wei; Li, Feng
Abstract: Lithium-sulfur (Li-S) batteries are highly appealing for the next-generation of energy storage because of their high energy density and low-cost features. However, the practical implementation of Li-S batteries has been hindered by fast performance degradation of the sulfur cathode, especially at a high cathode loading. Here, we propose a strategic design of binary graphene foam (BGF) as the cathode scaffold, with the incorporation of nitrogen-doped graphene and highly porous graphene. The nitrogen-doped graphene provides chemical adsorption sites for migrating polysulfides, and the highly porous graphene could increase the cathode conductivity and accelerate lithium ion transport. The freestanding foam-like cathode structure further offers a robust, interconnected, conductive framework to promote the redox reaction even at a high cathode loading. Therefore, the Li-S battery with the S/BGF electrode exhibits a high specific areal capacity over 10 mAh cm –2 and good cycling stability over 300 cycles. This approach offers insights into multifunctional electrode structure design, with targeted functions for high-performance Li-S batteries.